Treatment Strategy for Impending Instability in Spinal Metastases - Kim, Yeon Ho; Kim, Junho; Chang, Sam Yeol; Kim, Hyoungmin; Chang, Bong-Soon (Clinics in orthopedic surgery, 2020)
Determining surgical management of a spinal metastasis is difficult owing to the involvement of multiple factors. The spinal instability neoplastic score (SINS) system is a reliable tool to evaluate instability in spinal metastases. The intermediate SINS (scores 7-12) indicates impending instability, which makes it difficult to determine the proper treatment strategy. In this study, we aimed to compare the initial status and treatment outcomes of a conservative group versus an operative group among patients with spinal metastases with an intermediate SINS of 7-12. Further, we evaluated the time for conversion to surgery in patients who had initially undergone conservative treatment and identified the factors associated with the conversion. Among the patients with a spinal metastasis with an intermediate SINS of 7-12 from May 2013 to December 2017, those who were followed up for more than 12 months were enrolled in this study. Patients with signs of a neurologic deficit or cord compression at the initial diagnosis were excluded. Finally, 79 patients (47 in the initially conservative group and 32 in the initially operative group) were enrolled in this study. The performance status, Tomita score, and Tokuhashi score were assessed for group comparison. Components of SINS, the Bilsky grade, and radiosensitivity of tumor were evaluated to determine factors associated with conversion to surgery. Average follow-up was 20.9 months (range, 12-46 months). The demographic variables, primary cancer type, and performance status were not significantly different between the 2 groups. However, the Tomita score was lower in the initially operative group ( = 0.006). The 1-year treatment outcome assessed based on the change in performance status and vertebral height collapse showed a tendency to deteriorate less in the initially operative group. The rate of conversion to surgery in the initially conservative group was 33% in the first year, after which there was little change in the incidence of conversion. When vertebral body collapse was less than 50% or the tumor was located in the semi-rigid region (T3-T10), the need for conversion to surgery increased statistically significantly ( = 0.039 and = 0.042, respectively). The rate of conversion to surgery in initially conservatively treated patients was about 33% in the first year. When a tumor is located in T3-T10 and less than 50% vertebral body collapse is present, surgery may be the better choice than conservative treatment.